2000
DOI: 10.1159/000056736
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study on Red Cell Usage in Primary Total Knee Replacement Surgery

Abstract: Background and Objectives: There is wide variation in the use of red cell transfusions for the same clinical indication. The purpose of the study was to comment on preoperative and discharge haemoglobin (Hb) levels and perioperative blood loss, and to project the Hb level if transfusions were not administered. Materials and Methods: The case notes of 187 patients who underwent primary total knee replacement were reviewed retrospectively. Results: More than 90% of the transfusions were given in the immediate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Comparable analyses based on increasing the numbers of CABG surgery suggest more significant rises in demand for RBC units. The results from this more detailed orthopaedic study also revealed wide variation in transfusion practice, which has been noted in other studies, and which is also likely to apply in other high blood‐user specialties [12–14]. We have further extended this study to look at blood utilization in elective orthopaedic surgery in 200 hospitals in England.…”
Section: Discussionsupporting
confidence: 67%
“…Comparable analyses based on increasing the numbers of CABG surgery suggest more significant rises in demand for RBC units. The results from this more detailed orthopaedic study also revealed wide variation in transfusion practice, which has been noted in other studies, and which is also likely to apply in other high blood‐user specialties [12–14]. We have further extended this study to look at blood utilization in elective orthopaedic surgery in 200 hospitals in England.…”
Section: Discussionsupporting
confidence: 67%
“…In a previous studies, we found that USB return did not modify either the acute phase response or the cellular immune response to TKR [15,16], but it decreased the risk of receiving an ABT (48% vs. 11%, P < 0·01) and reduced the ABT index by 1 unit [9]. However, a transfusion protocol was not established, probably leading to unnecessary transfusions [17], as ABT rate in the control group was higher than that reported Data are expressed as mean ± SD, incidence or percentage. G, general anaesthesia; R, regional anaesthesia.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous studies, we found that USB return did not modify either the acute phase response or the cellular immune response to TKR [15,16], but it decreased the risk of receiving an ABT (48% vs. 11%, P < 0·01) and reduced the ABT index by 1 unit [9]. However, a transfusion protocol was not established, probably leading to unnecessary transfusions [17], as ABT rate in the control group was higher than that reported in recent TKR series [1,8,18,19]. In this present study, the introduction of a transfusion protocol (transfusion trigger, Hb < 9 g/dl) resulted in a reduction of ABT rate in patients managed without USB return with respect to our previous series (48% vs. 30·6%; relative risk (RR): 0·60, P < 0·01).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that a transfusion algorithm and a brief focused educational programme can substantially improve transfusion practice. Whilst only 30% of patients received blood in the present study, a retrospective survey carried out on a similar group of patients by the authors in the same institution showed a transfusion rate of 64% [8]. The patients were stratified into three groups, according to the preoperative Hb levels described in the algorithm, and the transfusion incidence between the prospective and retrospective studies were compared (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…Most of the transfusions given in the perioperative period are prescribed by junior surgical staff who could benefit from simple and explicit guidelines. We present the data on a prospective study in patients who underwent elective total knee replacement and compare the findings with a retrospective survey carried out by the authors [8]. The aims of the study were to assess the rate of compliance with a transfusion algorithm and evaluate its effect on transfusion practice.…”
Section: Introductionmentioning
confidence: 99%